Conductivity or rheology? Tradeoff for competing properties in the fabrication of a gel polymer electrolyte based on chitosan-barbiturate derivative - Azzahari, Ahmad Danial; Selvanathan, Vidhya; Rizwan, Muhammad; Sonsudin, Faridah; Yahya, Rosiyah (Springer Verlag (Germany), 2018)
Chitosan-barbiturate (Ch-Ba) derivative was synthesized to afford organosolubility. Attachment of Ba onto the Ch backbone was confirmed by 1 H NMR with peaks at 8.2 and 11.1 ppm, and FTIR with bands at 1679 and 1739 cm −1 belonging to the Ba ring. This derivative was used as a host polymer in the preparation of gel polymer electrolytes. The components of the gel consist of tetrapropylammonium iodide (TPAI) as the salt, SiO 2 nanofiller (NF) as the mechanical stabilizer, and dimethyl sulfoxide (DMSO) as the solvent. The necessary formulation required to produce the gel was studied using response surface models by means of artificial neural networks. Electrochemical and rheological behaviors were studied and the simulated model predicted conductivities were as high as 8.51 mS cm −1 while still maintaining a solid-like gel structure in the region where storage modulus dominated loss modulus, G″/G′ < 1.